Naturally Occurring Dominant Drug Resistance Mutations Occur Infrequently in the Setting of Recently Acquired Hepatitis C. Issue 2 (February 2015) - Applegate, Tanya L; Gaudieri, Silvana; Plauzolles, Anne; Chopra, Abha; Grebely, Jason; Lucas, Michaela; Hellard, Margaret; Luciani, Fabio; Dore, Gregory J; Matthews, Gail V
Background: Direct-acting antivirals (DAAs) are predicted to transform hepatitis C therapy, yet little is known about the prevalence of naturally occurring resistance mutations in recently acquired HCV. This study aimed to determine the prevalence and frequency of drug resistance mutations in the viral quasispecies among HIV-positive and -negative individuals with recent HCV. Methods: The NS3 protease, NS5A and NS5B polymerase genes were amplified from 50 genotype 1a participants of the Australian Trial in Acute Hepatitis C. Amino acid variations at sites known to be associated with possible drug resistance were analysed by ultra-deep pyrosequencing. Results: A total of 12% of individuals harboured dominant resistance mutations, while 36% demonstrated non-dominant resistant variants below that detectable by bulk sequencing (that is, <20%) but above a threshold of 1%. Resistance variants (<1%) were observed at most sites associated with DAA resistance from all classes, with the exception of sofosbuvir. Conclusions: Dominant resistant mutations were uncommonly observed in the setting of recent HCV. However, low-level mutations to all DAA classes were observed by deep sequencing at the majority of sites and in most individuals. The significance of these variants and impact on future treatment options remains to be determined. Clinicaltrials.gov NCT00192569.